(untitled) - Annette Roman (Washington, D.C., 2006)
Manga are Japanese-style comics or graphic novels which have become the rage among young readers around the world. Teaming up with Viz, the second largest English-language manga publisher, the Bank has launched a new series of comic books, each highlighting a key development issue. The stories follow the adventures of 15-year-old Rei who discovers that the only way to become a true warrior is to understand the challenges facing the poor and disadvantaged people he befriends along the way. Rei's humorous side-kick is a wise "spirit guide" which morphs into different animal guises as it introduces Rei to each new challenge. An appendix in each book provides further information, websites, and other resources so readers can explore the themes introduced in the story.
Keywords: Children literature